Numerical Simulation of Microstructure Evolution of Directionally Annealed Pure Iron by Cellular Automata - Rongyi Zhou; Xiaohui Feng; Ce Zheng; Qiuyan Huang; Yingju Li; Yuansheng Yang (Metals, 2023)
In order to understand the effects of drawing velocity, initial grain size and texture on the microstructure evolution during directional annealing, a cellular automata model based on grain boundary (GB) curvature, GB energy and GB mobility was established with a modified calculation model of the GB curvature. The simulation results show that there is a lower limit and an upper limit to the drawing velocity for the formation of columnar grains, and the columnar grains can only be formed between the upper limit and the lower limit. The simulation results are consistent with the experimental results. When the drawing velocity is lower than the lower limit, the equiaxed grains grow at the front of the hot zone, which hinders the formation of the columnar grains. With the increase of initial grain size, the driving force of GB migration decreases, and the grain boundaries are difficult to move with the hot zone, which is not conducive to the formation of columnar grains. There is an upper limit of initial grain size for the formation of columnar grains. The abnormal growth induced by texture prevents the growth of columnar grains during directional annealing. The weaker the texture strength, the more conducive to the growth of columnar grains.